Optically stimulated luminescence detectors for LET determination and dosimetry in ion beam therapy - Christensen, Jeppe Brage; Bossin, Lily; Muñoz, Iván Domingo; Stengl, Christina; Vedelago, José; Yukihara, Eduardo Gardenali (Radiation measurements, 2024)
Optically stimulated luminescence detectors (OSLDs) have been utilized for various dosimetry applications for many years. The use of Al2O3:C OSLDs for proton dosimetry began over a decade ago, taking advantage of the correlation between the ionization density of the radiation field and the ratio of intensities of the material’s two emission bands. The correlation allows for determining both linear energy transfer (LET) and dose in proton beams, with corrections for ionization quenching derived from the LET. However, the previous methodology for proton dosimetry and simultaneous LET determination with Al2O3:C OSLDs was cumbersome and occasionally associated with large uncertainties, while carbon beam dosimetry posed further challenges due to an elevated LET. This paper reviews the recent advancements in ion beam dosimetry and LET determination using OSLDs. Employing Al2O3:C,Mg OSLDs alongside improved, automatized read-out techniques, and the use of other radiation quality metrics than averaged LET, has removed most of the previous obstacles for ion beam dosimetry with OSLDs. The feasibility of simultaneous LET determination and dosimetry in ion beams is demonstrated through two case studies involving realistic proton and carbon ion therapy scenarios.
Online verfügbar: 13. August 2024, Artikelversion: 24. August 2024
Gesehen am 15.10.2024